Barnets rätt att bestämma i vården - En analys av svensk rätt och Europeiska rådets biomedicinkonvention - Comstedt,Felicia (2025)
The purpose of this essay is to analyse how children’s decision-making capacity in healthcare is regulated in Swedish law compared to the Council of Europe’s Convention on Human Rights and Biomedicine. Although Sweden has signed the convention, it has not yet been ratified, making it relevant to investigate how well Swedish law aligns with its rules and principles. The individual’s right to self-determination is essential in both Swedish law and the Biomedicine Convention and implementation of healthcare measures requires the patient’s informed consent. Both systems emphasize the right of the child to express his or her views in decisions concerning his or her healthcare. The child’s views must also be given due weight in accordance with their age and maturity. Swedish law lacks an explicit age limit for when a child can consent to care on their own. Instead, an individual assessment is made based on the child’s age and maturity, but the central aspect is whether the child has sufficient understanding of the measure’s meaning and its consequences. The Biomedicine Convention, on the other hand, should be seen as a framework convention and it’s for the national legal systems to decide how the decision-making capacity of the child should be decided. There are significant similarities between Swedish regulation and the convention’s provision, particularly the view of the child’s evolving autonomy and the fact that decisions concerning the child must be in their best interest. The Biomedicine Convention emphasizes the importance of national regulation containing a clear procedure regarding possible conflicts of interest between the child and the legal representative. Furthermore, the convention makes a clearer distinction between consent from the child and authorisation from a legal representative regarding the child. In conclusion, it is noted that Swedish law in many respects aligns with the purpose and principles of the Biomedicine Convention.
Keywords: komparativ rätt; medicinsk rätt; barnets bästa; beslutskompetens; bestämmanderätt; självbestämmande; mognadsbedömning; hälso- och sjukvård